Vocabulary learning strategies of Malaysian ESL students - Asgari, Azadeh; Mustapha, Ghazali (Universiti Putra Malaysia Press, 2012)
One of the most important challenges that learners face in second language learning is learning vocabulary. Vocabulary has been recognized as crucial to language use in which learners’ insufficient knowledge of vocabulary may lead to difficulties in their second language learning. Thus, in learning second language vocabulary, students need to be trained to use appropriate vocabulary learning strategies. This study examined vocabulary learning strategies(VLSs) used by Malaysian ESL students majoring in Teaching English as a Second Language (TESL) at Universiti Putra Malaysia. It is important to note that this is a population which has been rarely included in any previous studies on vocabulary learning strategies. Based on the aim of this study, it was decided that the best method for this investigation and to better understand the use of VLSs by these students was to adopt qualitative research design. For this purpose, open-ended interviewswereconducted individually with eight students at the Faculty of Educational Studies in UPM. The concluded strategies such as learning words through reading, the use of monolingual dictionary, the use of various English language media, and applying new English word in their daily speaking that are related to memory, determination, metacognitive strategies are popular strategies and learners are keen in using them.